Unpacking sources of comparative advantage: A quantitative approach - CHOR, Davin (Institutional Knowledge at Singapore Management University, 2010)
This paper develops an approach for quantifying the importance of different sources of comparative advantage, by extending the Eaton and Kortum (2002) model to predict industry trade flows. In this framework, comparative advantage is determined by the interaction of country and industry characteristics, with countries specializing in industries whose production needs they can best meet with their factor endowments and institutional strengths. I estimate the model parameters using: (i) OLS; and (ii) a simulated method of moments procedure that accounts for the prevalence of zeros in the bilateral trade data. I apply the model to explore various quantitative questions, such as how much distance, Ricardian productivity, factor endowments, and institutions each matter for country welfare in the global trade equilibrium.